Repenser le patrimoine, hier et aujourd’hui. Le génie de John Ruskin - Jérôme Bastianelli (Cahiers Victoriens et Edouardiens)
In his contribution Jérôme Bastianelli traces the history of the construction of the Crystal Palace and offers a stimulating parallel between John Ruskin’s view of the preservation of national heritage as exposed in his pamphlet written at the time of the inauguration of the building in 1854 and contemporary cultural heritage policies conducted in England and in France. He concludes with a reminder of Ruskin’s heritage theories on Marcel Proust.